CT Assessment of Subtypes of Pulmonary Emphysema in Mongolian Miners - Garamjav Khishigdavaa; Ichinnorov Dashtseren; Tuvshinjargal Dashjamts; Buyankhishig Lhagvatogoo; Naidan Nyamkhuu; Oyunchimeg Dookhuu; Gonchigsuren Dagvasumberel; Bayasgalan Gombojav (Central Asian Journal of Medical Sciences, 2020)
Objectives: To determine the incidence of subtypes of pulmonary emphysema identified by LDCT imaging and the relationship between emphysema subtypes with smoking and pulmonary function in miners. Methods: We reviewed 329 miners (245 men and 84 women). Each miner had a low dose (LD) chest CT. Among them 75 miners had a standard chest CT. The images were reconstructed using contemporary iterative reconstruction. Lung volumes and emphysema severity was calculated using automated densitometry segmentation software and qualitative visual analyses.There were two subtypes of pulmonary emphysema found: centrilobular emphysema (CLE) and paraseptal emphysema (PSE). Based on these subtypes, CLE was divided into the following five categories: trace, mild, moderate, confluent, and advanced CLE. PSE was divided into the following two catergories: mild and substantial PSE. Results: Pulmonary emphysema was found in 89 (27.1%) of 329 miners. According to the survey, 73 (82.0%) miners had centrilobulor emphysema, and 17 (18.0%) had a paraseptal emphysema. The emphysema group was a lower Gensler index than thenon-emphysema group. The smoker group had higher emphysematous changes than the non-smoker groups (p < 0.05). Conclusions: Dose reduced CT isauseful study for the assessment of emphysema.